Aplikasi Kitosan dari Litopenaeus vannamei dan Limbah Baglog dari Pleurotus ostreatus untuk Mendekolorisasi Limbah Cair Batik - Swastika Oktavia; Siti Rohmah; Cory Novi (Jurnal Penelitian Pendidikan IPA, 2024)
The batik sector generates wastewater containing pigment residue, posing a significant environmental threat if not managed effectively. L. vannamei shells yield chitin, convertible to chitosan for water treatment. Baglogs, comprising mycelium and cellulose, serve as a viable adsorbent. The purpose of this study was to learn about the use shell of L. vannamei and P. ostreatus baglog waste with different lengths of time to decolorization batik industry waste water. The method for testing involves deproteinization with NaOH 1M, demineralization with HCl 2M and deasetylation with NaOH 60%. Chitosan L. vannamei and baglog P. ostreatus (2:25 g/g) waste were put into a container containing 500 mL of batik wastewater with colour content with variations of 0, 12, 24, 48, 72, 96, and 120 hours. Further, the capacity of adsorption chitosan and baglog waste are determined using a UV-Vis spectrophotometer during the decolorization process in batik industry waste water using shell of L. vannamei and P. ostreatus baglog waste are 96 hours with a decolorization rate of 90.05%.